发布网友 发布时间:2024-10-22 12:39
共1个回答
热心网友 时间:2024-10-29 21:39
(1)∵Tn=1-an,an=TnTn-1,n≥2,
∴Tn=1-TnTn-1,从而1Tn-1Tn-1=1,(n≥2)
∴bn-bn-1=1,(n≥2)
∵T1=a1=1-a1,
∴a1=12,b1=1T1=1a1=2,
∴{bn}是以2为首项,1为公差的等差数列.
(2)由(1)知bn=2+(n-1)=n+1,从而cn=(n+1)?2n,
∴Sn=2?2+3?22+…+(n+1)?2n,
2Sn=2?22+3?23+…+n?2n+(n+1)?2n+1,
两式相减,得-Sn=4+(22+23+…+2n)-(n+1)?2n+1
=4+4(1-2n-1)1-2-(n+1)?2n+1
=-n?2n+1,
∴Sn=n?2n+1.
(3)∵Tn=1bn=1n+1,
∴n≥2时,an=TnTn-1=nn+1,
∵a1=12,∴an=nn+1,n∈N* ,
An=T12+T22+…+Tn2
=122+132+…+1(n+1)2
>
热心网友 时间:2024-10-29 21:37
(1)∵Tn=1-an,an=TnTn-1,n≥2,
∴Tn=1-TnTn-1,从而1Tn-1Tn-1=1,(n≥2)
∴bn-bn-1=1,(n≥2)
∵T1=a1=1-a1,
∴a1=12,b1=1T1=1a1=2,
∴{bn}是以2为首项,1为公差的等差数列.
(2)由(1)知bn=2+(n-1)=n+1,从而cn=(n+1)?2n,
∴Sn=2?2+3?22+…+(n+1)?2n,
2Sn=2?22+3?23+…+n?2n+(n+1)?2n+1,
两式相减,得-Sn=4+(22+23+…+2n)-(n+1)?2n+1
=4+4(1-2n-1)1-2-(n+1)?2n+1
=-n?2n+1,
∴Sn=n?2n+1.
(3)∵Tn=1bn=1n+1,
∴n≥2时,an=TnTn-1=nn+1,
∵a1=12,∴an=nn+1,n∈N* ,
An=T12+T22+…+Tn2
=122+132+…+1(n+1)2
>